A Comparative Study of Some Cellular Manufacturing Techniques - Low, W. K.; Osman, M. R.; M. Yusuff, Rosnah (Universiti Putra Malaysia Press, 2000)
Cellular manufacturing (CM) is a concept that involves processing of similar parts on dedicated cluster (or cells) of dissimilar machines or manufacturing processes. This paper concentrated on seven cell formation techniques used in Cellular Manufacturing (CM). The techniques were used to develop cells for matrices from various sizes of parts and machines. By randomly rearranging the sequence of the machines in the reference matrices (cited from published journals), 12 new matrices were developed. This paper also concentrated on performing the treatments for bottleneck, exceptional elements or voids using part subcontracting or machine duplication for the developed cells. The performance of each technique was measured using Grouping Measures (GM), where high percentage of GM indicates that the technique has high machine utilization (MU) and low percentage of exceptional elements (EE). Overall, Bond Energy Algorithm (BEA) was found to be the best cell formation technique.